1992
DOI: 10.1073/pnas.89.12.5477
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for in vitro replication of hepatitis C virus genome in a human T-cell line.

Abstract: A human T-cell line, MOLT-4, either uninfected or infected with murine retroviruses, was tested for its susceptibility to hepatitis -C virus (HCV) infection. The cell cultures were inoculated with a serum containin HCV and then examined for the presence of viral sequences by cDNA/PCR. In murine retrovirus-infected MOLT-4 (MOLT-4 Ma) cells, intracellular minus-strand viral RNA, a putative replication intermediate, was first detected 3 days after inoculation, and the maximum signal was seen on day 7. When the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
169
0
2

Year Published

1993
1993
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(176 citation statements)
references
References 21 publications
(16 reference statements)
5
169
0
2
Order By: Relevance
“…This finding is consistent with in vitro data that showed infection of human T (H9, HPBALL, and MOLT 4) and B (Daudi) cell lines by several HCV inocula, and a correlation between the efficacy of infection and levels of HCV viremia. [31][32][33][34][35][36] The detection of viral particles by electron microscopy confirmed further that such cells might support complete HCV multiplication. 37 These results are probably caused by the selection of permissive hematopoietic cell line clones and by the adaptation of an HCV strain to lymphatic cells in culture.…”
Section: Discussionmentioning
confidence: 76%
“…This finding is consistent with in vitro data that showed infection of human T (H9, HPBALL, and MOLT 4) and B (Daudi) cell lines by several HCV inocula, and a correlation between the efficacy of infection and levels of HCV viremia. [31][32][33][34][35][36] The detection of viral particles by electron microscopy confirmed further that such cells might support complete HCV multiplication. 37 These results are probably caused by the selection of permissive hematopoietic cell line clones and by the adaptation of an HCV strain to lymphatic cells in culture.…”
Section: Discussionmentioning
confidence: 76%
“…However, it is not yet clear whether T lymphocytes are infected in vivo, and this result might also be explained by a cross-contamination of B lymphocytes in the T lymphocyte subset. Shimizu et al (1992) recently reported an in vitro infection of a human T cell line (MOLT-4) containing minus-strand viral RNA. HCV replication, however, was demonstrated in a permanent T cell line and not in' normal' T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…63,78 There is also a growing body of evidence to suggest that HCV replication may occur within peripheral dendritic cells, granulocytes, B lymphocytes, and monocytes/macrophages. [79][80][81] While some of these data should be viewed cautiously, as a variety of techniques were utilized and a limited number of samples [82][83][84] Interestingly, sequence analysis has subsequently revealed that certain viral variants may be selected for growth in extrahepatic cell types, implying that HCV diversity directly impacts cell tropism. 85,86 Furthermore, several studies have described a non-random distribution of HCV sequences in hepatic and extrahepatic compartments, 72,[87][88][89][90][91][92][93][94][95][96] leading to the conclusion that the presence of tissue-specific sequences is compatible with independent viral replication in extrahepatic sites.…”
Section: Evidence For Extrahepatic Replication Of Hcvmentioning
confidence: 99%